ECG-gated cardiac MDCT for detection of systolic anterior motion of mitral valve. (September 2013) - Ghersin, Eduard; Castellon, Ivan; Runco Therrien, Jennifer E.; Tanawuttiwat, Tanyanan; Lessick, Jonathan; Checkver, Adam; Soto, Victor
Abstract: Objectives: Evaluating ECG-gated cardiac MDCT detection of systolic anterior motion of the mitral valve, in comparison to trans-thoracic echocardiography as a gold standard. Materials and methods: Study group included 83 consecutive patients (57 men; average age 56.1 years) evaluated with both retrospective ECG-gated cardiac MDCT and trans-thoracic echocardiography within an interval of 30 days. ECG-gated cardiac MDCT imaging was performed with retrospective ECG- gating using 64-slice and 128-slice CT scanners with an inherent temporal resolution range of 75–165 ms. MDCT's and trans- thoracic echocardiograms were retrospectively and independently evaluated by experienced radiologist and cardiologist respectively, for presence of systolic anterior motion of the mitral valve. Results: 7 patients (8.4%) were found to have systolic anterior motion by trans-thoracic echocardiography, from which 6 were found to have systolic anterior motion by ECG-gated cardiac MDCT. Of the 76 patients without systolic anterior motion on trans-thoracic echocardiography, all were correctly identified using ECG-gated cardiac MDCT. The sensitivity, specificity, positive and negative predictive values and accuracy of ECG-gated cardiac MDCT in identifying systolic anterior motion of the mitral valve were 85.7% (6/7), 100% (76/76), 100% (6/6), 98.7% (76/77) and 98.8% (82/83), respectively. Conclusion: ECG-gated cardiac MDCT is comparable to trans-thoracic echocardiography in detecting systolic anterior motion of the mitral valve.